Magnesium/Calcium Ratio in Serum Predicts Periodontitis and Tooth Loss in a 5-Year Follow-up. (October 2016) - Meisel, P.; Pink, C.; Nauck, M.; Jablonowski, L.; Voelzke, H.; Kocher, T.
In the cross-sectional Study of Health in Pomerania (SHIP-0), subjects with an adequate magnesium supply had a lower risk of periodontal disease and more teeth than those with low magnesium levels. The authors analyzed 5-y follow-up data (SHIP-1) to determine whether the baseline magnesium levels had a long-term effect on attachment level and number of teeth lost. Of the participants examined dentally in the baseline study, 3, 300 (75%) were examined for progression or recession of periodontal attachment level after 5 y. For 2, 432 subjects, the authors related the outcome variables of periodontal attachment level and tooth loss to baseline characteristics, especially serum magnesium and calcium concentrations, as well as systemic markers of inflammation. The progression of periodontitis was associated with the magnesium/calcium (Mg/Ca) ratio at baseline in a dose-dependent manner. Progression of mean attachment loss was prevented in the upper quartile of the Mg/Ca ratio ( P < 0.001) with antagonistic effects of magnesium and calcium irrespective of inflammatory state. With respect to tooth loss, Mg/Ca exerted dimorphic effects. In inflammatory states as indicated by high C-reactive protein (>3 mg/L), tooth loss was prevented in subjects with high Mg/Ca ratio (incidence rate ratio = 0.60, 95% confidence interval: 0.45 to 0.80, P = 0.001), but the contrary was observed in subjects with low C-reactive protein levels (incidence rate ratio = 1.14, 95% confidence interval: 0.97 to 1.34, NS). Similar results were observed with stratifying the regression on tooth loss by interleukin 6 or fibrinogen threshold. An adequate magnesium serum level and Mg/Ca balance may prevent progression of attachment level and tooth loss, especially in inflammatory states. Knowledge Transfer Statement: The results of this study present evidence that an adequate magnesium supply may be important in the prevention of periodontal diseases and future tooth loss. A diet high in magnesium could improve periodontal health, notwithstanding its beneficial effects on systemic disease. In populations with a high prevalence of hypomagnesemia, additional intake of supplements is advisable.